Comparison of density functional and modified Poisson-Boltzmann structural properties for a spherical double layer - Bhuiyan, L.B.; Outhwaite, C.W. (Condensed Matter Physics, 2005)
The density functional and modified Poisson-Boltzmann descriptions of a spherical (electric) double layer are compared and contrasted vis-a-vis existing Monte Carlo simulation data (for small ion diameter 4.25 · 10⁻¹⁰ m) from the literature for a range of physical parameters such as macroion surface charge, macroion radius, valencies of the small ions, and electrolyte concentration. Overall, the theoretical predictions are seen to be remarkably consistent between themselves, being also in very good agreement with the simulations. Some modified Poisson-Boltzmann results for the zeta potential at small ion diameters of 3 and 2 · 10⁻¹⁰ m are also reported.